ANALYSIS OF SERVICE BASED ON EXCELLENT SERVICE IN INCREASING CUSTOMER SATISFACTION AT EVA PERMATA KONAWE UTARA RESTAURANT - Rasna, Rasna; Razak, Abdul; Supriaddin, Nofal (Penelitian dan Pengembangan Ilmu, 2024)
Service quality is a crucial factor in increasing customer satisfaction, especially in the competitive restaurant industry. However, the challenge in maintaining service consistency, especially in the dimensions of reliability and responsiveness, is a problem that is often faced by restaurants, including Eva Permata Restaurant. This research fills the knowledge gap by exploring the implementation of service excellence based on the SERVQUAL dimension (reliability, assurance, tangibles, empathy, and responsiveness) to improve service quality. The qualitative descriptive methodology is used through in-depth interviews, observations, and document reviews with informants that include managers, employees, and regular customers. The results of the study show success in the dimensions of assurance, tangibles, and empathy, while the dimensions of reliability and responsiveness require improvement, especially in operational management during crowded conditions. This research makes a theoretical contribution to the SERVQUAL literature in the restaurant industry and offers practical solutions in the form of strengthening SOPs, competency-based training, and the use of technology. By strengthening areas that need attention, this research can be a strategic reference to improve customer satisfaction holistically in the restaurant sector.